Differential effects of speed on two-dimensional foot strike pattern during barefoot and shod running in recreationally active men. Issue 4 (3rd July 2020) - Wang, Ran; Fukuda, David H.; Cheng, Peng; Hu, Yang; Stout, Jeffrey R.; Hoffman, Jay R.
ABSTRACT: The majority of barefoot running studies have not considered speed as an influential factor on foot strike pattern. The aim of this study was to investigate differences in foot strike pattern and spatiotemporal characteristics between barefoot and shod overground running at varying speeds. We first determined maximal running speed (Vm) over 50 m in 15 recreationally active men who self-reported as habitual rearfoot strikers. Participants then completed shod and barefoot running trials at different speeds equivalent to approximately 90%, 80%, 70% and 60% of Vm. Sagittal plane two-dimensional (2D) foot-ground contact angle, ankle plantar-dorsi flexion angle, contact time, flight time, step length and step rate variables for each trial were recorded. A significant interaction effect of running speed and footwear condition ( p  < 0.05) on foot-ground contact angle, ankle plantar-dorsi flexion angle and contact time was observed. There was a main effect of running speed ( p  < 0.01) on flight time, step length and step rate. There was a main effect of footwear condition on step length ( p  < 0.01). Participants were more inclined to plantarflex the ankle and contact the ground with the forefoot at higher percentages of Vm, especially when running barefoot.